Microsoft Windows 8 - Rusen, Ciprian Adrian; Ballew, Joli (Delhi PHI Learning, 2013)
Quickly teach yourself new ways to work with Windows on your PC and touch-enabled devices. Learn to explore the Start screen and use touch on tablets; connect your home network, email and social media; customize your experience with cool apps; manage photos, music, movies, and connect to Xbox; organize files and folders, and store them in the cloud; and help secure, troubleshoot, and tune your system.
Includes index
Keywords: Microsoft Windows (Computer file); Operating systems (Computers)